Modern Vasopressor Therapy of Septic Shock (Review) - A. A. Kochkin; A. G. Yavorovskiy; L. B. Berikashvili; V. V. Likhvantsev (Общая реаниматология)
Septic shock, as the most severe form of sepsis, is characterized by high mortality reaching 40% despite the use of the most modern standards of diagnosis and treatment. In the thanatogenesis of septic shock, vasoplegia plays a leading role, respectively, and therapy of the condition under discussion involves the use of vasoconstrictors, along with the standard prescription of infusion therapy, antibiotics and symptomatic treatment. The choice of a specific vasoactive drug is a difficult task for a practicing anesthetist, as along with undoubtedly positive properties, vasoconstrictors each have their own spectrum of undesirable side effects, which, of course, must be taken into account when determining treatment tactics.The aim of review: A comprehensive assessment of the multifactorial effect of various vasoconstrictors on the patient to determine the criteria for choosing the optimal drug (or a combination of drugs) in septic shock.The search was carried out using PubMed and Scopus databases, the final selection of 89 articles was carried out in accordance with the following criteria: relevance to the topic of this review and the nature of the article — only randomized controlled trials, guidelines and analytical reviews were included in the final analysis.External and internal mechanisms of vascular tone regulation are considered, including factors produced by endothelium (nitric oxide, prostacyclin, endothelin); vasoactive metabolites and autocoids — signal molecules of local action (serotonin, prostaglandins, thromboxane A2). Accordingly, drugs were analyzed the mechanism of action of which is related to the effect on adrenergic (adrenaline, dopamine, norepinephrine, phenylephrine, dobutamine), vasopressin (vasopressin, terlipressin, selepressin) receptors, synthetic analogues of angiotensin (angiotensin II) and drugs the non-vasopressor effect of which is not linked with the receptor apparatus (methylene blue, levosimendan, hydrocortisone).Conclusion. The high effectiveness of norepinephrine, its positive hemodynamic effects make the drug under discussion, in many ways, a universal remedy for the relief of septic shock. However, refractory shock may require the introduction of such high doses of norepinephrine that the occurrence of adverse reactions will become practically inevitable. The combined use of adrenergic and ligand V receptors, terlipressin, is intended to prevent these complications. However, to date, there are no clear recommendations on the use of terlipressin in septic shock, which limits its use in clinical practice.